Women's Experience Obtaining Abortion Care in Texas after Implementation of Restrictive Abortion Laws: A Qualitative Study. - Sarah E Baum; Kari White; Kristine Hopkins; Joseph E Potter; Daniel Grossman (PLoS ONE, 2016)
In November 2013, Texas implemented three abortion restrictions included in House Bill 2 (HB 2). Within six months, the number of facilities providing abortion decreased by almost half, and the remaining facilities were concentrated in large urban centers. The number of medication abortions decreased by 70% compared to the same period one year prior due to restrictions on this method imposed by HB 2. The purpose of this study was to explore qualitatively the experiences of women who were most affected by the law: those who had to travel farther to reach a facility and those desiring medication abortion.In August and September 2014, we conducted 20 in-depth interviews with women recruited from ten abortion clinics across Texas. The purposive sample included women who obtained or strongly preferred medication abortion or traveled ≥50 miles one way to the clinic. The interview guide focused on women's experiences with obtaining services following implementation of HB 2, and a thematic analysis was performed.Women faced informational, cost and logistical barriers seeking abortion services, and these obstacles were often compounded by poverty. Two women found the process of finding or getting to a clinic so onerous that they considered not having the procedure, although they ultimately had an abortion; another woman decided to continue her pregnancy, in part because of challenges in getting to the clinic. For two women, arranging travel required disclosure to more people than desired. Women who strongly preferred medication abortion were frustrated by the difficulty or inability to obtain their desired method, especially among those who were near or just beyond the gestational age limit. The restricted eligibility criteria for medication abortion and difficulty finding clinics offering the method created substantial access barriers.Medication abortion restrictions and clinic closures following HB 2 created substantial barriers for women seeking abortion in Texas.